Good Girl, Bad Blood - Jackson,Holly (London Electric Monkey, An imprint of Harper Collins Publisher, 2020)
Pip Fitz-Amobi is not a detective anymore. With the help of Ravi Singh, she released a true-crime podcast about the murder case they solved together last year. The podcast has gone viral, yet Pip insists her investigating days are behind her. But she will have to break that promise when someone she knows goes missing.
Keywords: Mystery- Fiction -- Murder-Fiction